Hubungan Beban Kerja dan Kepuasan Kerja dengan Kinerja Karyawan Instalasi Rekam Medis di RSUD Cut Meutia Lhokseumawe - Manisha Manisha; Cut Aila Azzura; Yuniati Yuniati (Pusat riset dan Inovasi Nasional, 2025)
Minister of Health Regulation No. 269 of 2008 explains that medical records are defined as a collection of documents containing complete information regarding patient identity, examination results, therapy, medical procedures, and health services received. In working, an employee should be able to balance their workload to achieve work harmony that contributes to increased productivity. Job satisfaction reflects the appreciation and comfort felt by an individual for the tasks they perform. Conversely, dissatisfaction at work can trigger negative reactions in the form of aggressive behavior or a tendency to withdraw from social interactions around them. Job satisfaction also greatly influences employee motivation and commitment to continue working with enthusiasm and achieve the desired goals. The purpose of this study was to determine the relationship between workload and job satisfaction with employee performance in the Medical Records Installation of Cut Meutia Hospital, Lhokseumawe in 2023. The research method was an analytical survey with a cross-sectional approach. The study was conducted at Cut Meutia Hospital, Lhokseumawe from September to December 2023. The study population was 40 Medical Records Installation employees. The sampling technique used total sampling, namely 40 respondents. Data analysis used univariate analysis and bivariate analysis. The results of the study based on the chi-square test showed a relationship between workload and employee performance at the Medical Records Installation of Cut Meutia Hospital, Lhokseumawe with a p-value = 0.001 <0.05 and a relationship between job satisfaction and employee performance at the Medical Records Installation of Cut Meutia Hospital, Lhokseumawe with a p-value = 0.000 <0.05. Conclusion; The conclusion in the study is that there is a relationship between workload and job satisfaction with employee performance at the Medical Records Installation of Cut Meutia Hospital, Lhokseumawe in 2023.